TEMPORARY IMMEDIATE FACIAL NERVE PALSY AFTER LOCAL ANESTHESIA INJECTION FOR THE REPAIR OF EAR LACERATION - Vasandani, Rajesh K.; Farooqui, Sofia; Mehfooz, Sana; Khan, Tariq Zahid; Ahmed, Zeba; Siddiqui, Fatima (Pakistan Armed Forces Medical Journal, 2021)
Peripheral facial nerve paralysis constitutes a rare side effect of local anesthesia. The previously reported cases mainly constituted patients operated for dental and oro-maxillofacial procedures, but not commonly encountered in ear laceration repair. The literature suggests that only one or two of its branches get affected in the postoperative period, and complete involvement of facial nerve never occurred. We report a case of unilateral facial nerve paralysis immediately following the administration of local anesthesia (lidocaine 1% with adrenaline 1:100,000) in a rhomboid block prior to suturing a laceration of the left pinna, followed by full recovery within the next 4 hours without any surgical intervention. To our knowledge, no similar data has been published till date considering the minimal amount of local anesthesia used, and complete involvement of facial nerve even after injecting it away from the main nerve trunk.